Mitigating IS Implementation Challenges in Government Hospitals through Integrated Change Management Approach - Sanmuga Raja, Jeviena Rani; Nur Iffah Syamilah Mohd Radzi,; Alya Humaira Syahmi Tarmizi,; Khairul Anwar Ahmad Sayuthi,; Muhammad Harith Haikal Mohd Hafiz,; Mohamad Aizi Salamat, (Applied Information Technology And Computer Science, 2023)
This study highlights how important change management (CM) is to the effective adoption of information systems (IS) in public hospitals. An integrated preventative approach that incorporates Lewin, Kotter, and Prosci techniques is suggested in light of the difficulties associated with the adoption of IS. The essay highlights the importance of managing time, money, scope, and risk and emphasizes the necessity for a complete strategy to reduce implementation issues. The concept encompasses pre-, during-, and post-implementation stages and aims to manage user resistance, encourage commitment, and guarantee ongoing integration. With the goal of preventing project failure and increasing efficiency, it provides strong guidelines for IS project managers and healthcare administrators. Future studies should look into ways to overcome infrastructure and technological limitations in order to successfully integrate IS and promote organization expansion.